(untitled) (Journal of Foreign Language Studies, 2024)
Listening comprehension poses many challenges to beginners in learning a foreign language. In this article, factors affecting listening comprehension will be discussed, including speaking style/accents, rhythms, auditory decoding, types of audiovisual texts, and tasks in the listening process from the perspectives of linguists such as Brown, Mueller, Eykyn, and Vygotsky. The article helps orient and improve the teaching and learning of listening comprehension in foreign languages in general, and in French language in particular.